تقييم التطوير الإداري لدى الأندية الرياضية في محافظة نينوى من وجهة نظر أعضاء الهيئات الإدارية - الدباغ، محمد خالد أحمد (جامعة تكريت - كلية التربية البدنية وعلوم الرياضة, 2022)
هدف البحث الحالي إلى: - بناء مقياس التطوير الإداري للأندية الرياضية في محافظة نينوى من وجهة نظر أعضاء الهيئات الإدارية وكذلك التعرف على التطوير الإداري للأندية الرياضية في محافظة نينوى من وجهة نظر أعضاء الهيئات الإدارية فيها، اشتمل مجتمع البحث على أعضاء الهيئة الإدارية للأندية الرياضية في محافظة نينوى، والذين تم اختيارهم بالطريقة العمدية لتحقيق أهداف البحث، والبالغ عددهم (230) عضو هيئة إدارية، إذ حاول الباحث استخدام أسلوب الحصر الشامل في اختيار أفراد المجتمع لتحقيق أهداف البحث، وبناء مقياس متكامل من جميع الجوانب. أما عينة البحث عينة بناء المقياس) فقد تمثلت بأعضاء الهيئات الإدارية للأندية الرياضية في محافظة نينوى، إذ تم الحصول على إجابات (160) إداريا، وذلك بعد استبعاد عينة الثبات والتجربة الاستطلاعية للمقياس وبعض الاستمارات غير مكتملة الإجابة، وبذلك بلغت نسبة عينة البحث (69%) من المجتمع الكلي للبحث. وقد بلغ المقياس بصورته النهائية من (44) فقرة وذلك بعد حذف (6) فقرة حسب أسلوبي المجموعتين المتطرفتين والاتساق الداخلي. واستنتج الباحثان ما يأتي: - بناء مقياس التطوير الإداري للأندية الرياضية في محافظة نينوى من وجهة نظر أعضاء الهيئات الإدارية، والذي يتكون من (44) فقرة، تتمتع بالصدق والثبات. - امتلاك الأندية الرياضية في محافظة نينوى التطوير الإداري. ويوصي الباحثان بما يأتي: - اعتماد المقياس المعد في معرفة التطوير الإداري للأندية الرياضية في محافظة نينوى من وجهة نظر أعضاء الهيئات الإدارية لهذه الأندية الرياضية في محافظة نينوى. - إجراء دراسة ارتباطية بين درجة عضو الهيئة الإدارية في المقياس المعد في هذا البحث وبين ترتيب الأندية الرياضية حسب البطولات التي تشارك بها هذه الأندية. Building a scale of administrative development for sports clubs in Nineveh Governorate from the point of view of members of the administrative bodies, as well as identifying the administrative development of sports clubs in Nineveh Governorate from the point of view of members of the administrative bodies therein. The research community included members of the administrative body of sports clubs in Nineveh Governorate, who were selected In the intentional way to achieve the objectives of the research, the number of which is (230) administrative body members, as the researcher tried to use the comprehensive inventory method in selecting members of the community to achieve the objectives of the research, and build an integrated scale. As for the research sample (the scale building sample), it was represented by members of the administrative bodies of sports clubs in Nineveh Governorate, as (160) administrative answers were obtained, after excluding the stability sample and the exploratory experience of the scale and some incomplete forms for the answers, and thus the proportion of the research sample reached (69%) from the entire research community. In its final form, the scale reached(44)items after deleting(6)items according to methods of the two extreme groups and internal consistency. The researchers concluded the following: - Building the measure of administrative development for sports clubs in Nineveh Governorate from the point of view of members of the administrative bodies, which consists of (44) paragraphs, enjoying honesty and stability. -Owning sports clubs in Nineveh Administrative development The researchers recommend the following: - Adopting the scale prepared in the knowledge of the administrative development of sports clubs in Nineveh Governorate. - Conducting a correlational study between the degree of a member of the administrative body in the scale prepared in this research and the ranking of sports clubs according to the championships in which these clubs participate
Keywords: القيادات الإدارية -- التطوير الإداري -- السلوك التنظيمي -- المؤسسات الرياضية